"The Mighty Delaware" lecture slides - Interstate Commission on the Delaware River Basin (1954)
Script for a lecture likely presented by the Interstate Commission on the Delaware River Basin (INCODEL), a water conservation organization that included New York, New Jersey, Pennsylvania, and Delaware. In 1961, a new partnership between those four states and the federal government—the Delaware River Basin Commission—replaced INCODEL. The lecture served the purpose of pitching INCODEL's environmental conservation programs. The presentation begins by establishing the importance of the river and describing its uses and influences across the region. It introduces the risk of pollution to the river by human activities, and the programs instituted by the Commission to address the risks including the Basin-Wide Pollution Abatement Program, the Schuykill River Restoration Project, Co-operative Reforestation Project, and others. The slides include photographic views showing different vistas of the river and surrounding environment, as well as slides containing textual information. The Delaware River Basin Commission was the first partnership between the federal government and individual states to manage the resources of a river basin. The agency predates the establishment of the United States Environmental Protection Agency (1970) and the Clean Water Act (1972). The Commission exists today and conducts programs related to water quality protection, water supply allocation and water conservation, watershed planning, drought management, flood mitigation and loss reduction, and recreational activities
Keywords: Delaware River Basin Commission; United States--Delaware River; United States--Delaware River Valley; United States--Delaware River Watershed; Water conservation; Water conservation projects; Interstate Commission on the Delaware River Basin